Grey matter atrophy in patients with benign multiple sclerosis. Issue 7 (28th June 2022) - Niiranen, Marja; Koikkalainen, Juha; Lötjönen, Jyrki; Selander, Tuomas; Cajanus, Antti; Hartikainen, Päivi; Simula, Sakari; Vanninen, Ritva; Remes, Anne M.
Abstract: Background: Brain atrophy appears during the progression of multiple sclerosis (MS) and is associated with the disability caused by the disease. Methods: We investigated global and regional grey matter (GM) and white matter (WM) volumes, WM lesion load, and corpus callosum index (CCI), in benign relapsing‐remitting MS (BRRMS, n = 35) with and without any treatment and compared those to aggressive relapsing‐remitting MS (ARRMS, n = 46). Structures were analyzed by using an automated MRI quantification tool (cNeuro®). Results: The total brain and cerebral WM volumes were larger in BRRMS than in ARRMS ( p = .014, p = .017 respectively). In BRRMS, total brain volumes, regional GM volumes, and CCI were found similar whether or not disease‐modifying treatment (DMT) was used. The total ( p = .033), as well as subcortical ( p = .046) and deep WM ( p = .041) lesion load volumes were larger in BRRMS patients without DMT. Cortical GM volumes did not differ between BRRMS and ARRMS, but the volumes of total brain tissue ( p = .014) and thalami ( p = .003) were larger in patients with BRRMS compared to ARRMS. A positive correlation was found between CCI and whole‐brain volume in both BRRMS ( r = .73, p < .001) and ARRMS ( r = .80, p < .01). Conclusions: Thalamic volume is the most prominent measure to differentiate BRRMS and ARRMS. Validation of automated quantification of CCI provides an additional applicable MRI biomarker to detect brain atrophy in MS. Abstract : We investigated global and regional grey matter (GM) and white matter (WM) volumes, WM lesion load, and corpus callosum index (CCI), in benign relapsing.]remitting MS (BRRMS, n = 35) with and without any treatment and compared those to aggressive relapsing.]remitting MS (ARRMS, n = 46). Structures were analyzed by using an automated MRI quantification tool (cNeuro®). In our study thalamic volume was the most prominent measure to differentiate BRRMS and ARRMS. Validation of automated quantification of CCI provides an additional applicable MRI biomarker to detect brain atrophy in MS.